2022
DOI: 10.1177/17480485221074848
|View full text |Cite
|
Sign up to set email alerts
|

#RumorsCOVID-19: Predicting the Forwarding of Online Rumors in Wuhan, China and in Israel

Abstract: COVID-19 ushered in almost unprecedented socioeconomic and political challenges. A typical social reaction during such emergencies is rumormongering, which has intensified since the advent of social media. This study explored factors affecting users’ willingness to spread pandemic-related rumors in Wuhan, China and Israel. We tested a multi-variant model of factors affecting the forwarding of COVID-19 rumors. In an online survey conducted in April–May 2020, users of each country's leading social media platform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Sense of Security was measured through a 4-item scale which was adapted from Prentice et al, 51 Shamim et al, 76 and Archer et al. 77 Ariel et al’s 78 3-items scale was adapted for measuring rumors about COVID-19. Information and stimulation experience of COVID-19 mobile ringtone were measured through 4-items and 6-items respectively and the tool was adapted from Calder and Malthouse 43 and Malthouse et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sense of Security was measured through a 4-item scale which was adapted from Prentice et al, 51 Shamim et al, 76 and Archer et al. 77 Ariel et al’s 78 3-items scale was adapted for measuring rumors about COVID-19. Information and stimulation experience of COVID-19 mobile ringtone were measured through 4-items and 6-items respectively and the tool was adapted from Calder and Malthouse 43 and Malthouse et al.…”
Section: Methodsmentioning
confidence: 99%
“…The tool for panic buying behavior was adapted from the study of Lins and Aquino, 75 and it was measured through 7 items. Sense of Security was measured through a 4-item scale which was adapted from Prentice et al, 51 Shamim et al, 76 and Archer et al 77 Ariel et al’s 78 3-items scale was adapted for measuring rumors about COVID-19. Information and stimulation experience of COVID-19 mobile ringtone were measured through 4-items and 6-items respectively and the tool was adapted from Calder and Malthouse 43 and Malthouse et al 79 Finally, the marker variable was measured through a 3-item scale and was adopted from the study of Miller and Simmering.…”
Section: Methodsmentioning
confidence: 99%
“…A survey found that the lack of a reliable news resource was considered the most common cause of rumors (63.6%) (Banakar et al, 2021). Ariel et al (2022) discovered that individual drives, shaped by personal needs and degree of negative feelings, were the leading factors behind rumormongering. Generally, rumors arise in situations that are personally relevant but ambiguous or cognitively unclear and when credible explanations are not available from traditional sources, such as mass media, government agencies, or corporate management (Bordia & Difonzo, 2004).…”
Section: Rumor Transmissionmentioning
confidence: 99%
“…This combination of high consumption of media sources during the outbreak might result with stress enhancing and anxiety amplification (Levkovich and Shinan-Altman, 2021). Even though many media outlets and platform were available during the time of crisis, it was evident, that for Israeli citizens, WhatsApp was the leading text messaging application and social network for personal and professional needs during time of lockdowns and the pandemic (Ariel et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%